2021
DOI: 10.2186/jpr.jpor_2019_567
|View full text |Cite
|
Sign up to set email alerts
|

Association between oral health and sarcopenia: A literature review

Abstract: Purpose: Sarcopenia has recently been attracting attention as an early sign of the need for nursing care in older adults. Some studies have reported that oral health is related to sarcopenia and its diagnostic factors (hand grip strength, walking speed, and skeletal muscle mass). However, the relationship between oral health and sarcopenia remains poorly investigated and no review to date has compiled the available research on this relationship. The aim of this review was to summarize the current evidence desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 49 publications
(125 reference statements)
1
33
0
6
Order By: Relevance
“…Reduced occlusal force, decreased tongue pressure, decreased masticatory function, and deterioration of the swallowing function were significantly more common in the frailty group, a result that matches that of past research. Meanwhile, existing reports on the relationship between sarcopenia and occlusal force assessed using number of teeth or pressure indicating film have not yielded consistent results [ 33 ]. For example, in two directly contradictory reports, Tanaka et al [ 10 ] found a significant relationship between the number of teeth and sarcopenia, but no significant difference in the relationship between sarcopenia and occlusal force measured via pressure-indicating film.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced occlusal force, decreased tongue pressure, decreased masticatory function, and deterioration of the swallowing function were significantly more common in the frailty group, a result that matches that of past research. Meanwhile, existing reports on the relationship between sarcopenia and occlusal force assessed using number of teeth or pressure indicating film have not yielded consistent results [ 33 ]. For example, in two directly contradictory reports, Tanaka et al [ 10 ] found a significant relationship between the number of teeth and sarcopenia, but no significant difference in the relationship between sarcopenia and occlusal force measured via pressure-indicating film.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only one study has reported that handgrip strength is positively associated with masticatory performance measured with gummy jellies [ 7 ]. A recent review speculated that the mechanisms of the association between oral health and sarcopenia involve three pathways in which worsening of oral health causes poor dietary intake, neuromuscular system failure, and a loss of muscle strength caused by inflammation [ 6 ]. Meanwhile, we found associations between NT and a decline in handgrip strength, or possible sarcopenia, after adjusting for all confounders.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review reported an association between oral health and sarcopenia [ 6 ]. Some studies have reported that the number of remaining teeth and/or objective masticatory performance is related to handgrip strength, skeletal muscle mass, or sarcopenia [ 4 , 7 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis of 27 studies reviewed, a possible association between oral health status and sarcopenia was found; however, most of the studies included in this analysis were cross-sectional studies in Japan, and the results therefore are not representative [23] .…”
Section: The Relationship Between Tooth Loss and Sarcopeniamentioning
confidence: 92%